Origin of the High-K Tertiary magmatism in Northern Greece: Implications for mantle geochemistry and geotectonic setting. - Pipera, K.; Koroneos, A.; Soldatos, T.; Poli, G.; Christofides, G. (Bulletin of the Geological Society of Greece, 2013)
Tertiary plutonic and volcanic rocks cropping out in the Rhodope Massif (N. Greece) are studied using existing and new geochemical and isotopic data. Most of these rocks belong to the post-collisional magmatism formed as part of the prolonged extensional tectonics of the Rhodope region in Late Cretaceous– Paleogene time. This magmatism is considered to be of mantle origin; however, the character of the mantle source is controversial. Rock bulk chemistry and compositional variations show magmas with calc-alkaline to high-K calc-alkaline and shoshonitic features associated with magmatism at convergent margins. Initial 87Sr/86Sr, 143Nd/144Nd ratios, Pb isotopes and REE composition of the mafic rocks indicate mainly an enriched mantle source, even if some rocks indicate a depleted mantle source. Low- and High-K mafic members of these rocks coexist indicating a strongly heterogeneous mantle source. The High-K character of some of the mafic rocks is primarily strongly related to mantle enrichment by subduction-related components, rather than crustal contamination. The geochemical characteristics of the studied rocks (e.g Ba/Th,Th/Yb,Ba/La, U/Th, Ce/Pb) indicate that primarily sediments and/or sediment melts, rather than fluid released by the subducted oceanic crust controlled the source enrichment under the Rhodope Massif.